Evaluation of a preventive educational program for malocclusions: 7-year study - Beatriz Brandão SCARPELLI; Sandrine Bittencourt BERGER; Marília Franco PUNHAGUI; Cássio Alexandre Zeri de OLIVEIRA; Antonio FERELLE; Paula Vanessa Pedron OLTRAMARI-NAVARRO
Abstract This study aimed at evaluating the Protocol for the Prevention of Malocclusions (PPM), established in the preventive educational program developed by the Public Infant Oral Health Program of the State University of Londrina (PIOHP-UEL). Guardians of three-year-olds or older, maintaining nutritive (bottle) and/or non-nutritive (pacifier and finger) sucking habits, attended meetings designed to alert and guide them to eliminating these habits from their children. PPM patient records (2006-2013) were assessed and the data were described and evaluated by the Chi-square test, with a 5% significance level. Results 506 of the 802 guardians/children referred to the PPM joined. As for the children, the most frequently assessed habits were: bottle (56.1%), bottle and pacifier (18.4%), finger (11.9%), bottle and finger (7.1%), pacifier (5.7%), pacifier and finger (0.6%), and bottle/pacifier/finger (0.2%). After parent participation in the meetings, 335 (66.2%) children abandoned their habits. There was a statistical difference between type of oral habit and time to abandonment (p = 0.0001). However, those with only one habit abandoned it more easily (72.6%) than those with two or more associated habits (48.1%) (p = 0.042). Presence or absence of breastfeeding and parents' level of education had no significant effect on habit abandonment. Conclusion PPM was an important tool for spreading knowledge to guardians, greatly contributing to the abandonment of deleterious oral habits. Bottle sucking warrants special attention - mentioned by 81.8% of parents - either alone or associated with other habits. Thus, educational actions to implement the children's approach to oral health are fundamental to making behavioral changes and promoting education of healthy habits, thereby keeping malocclusions from developing.